Issues regarding the composition of capital flows - Williamson, John (2001)
Considers the composition of capital flows to developing countries. Argues that accessing FDI, portfolio equity or long-term loans, as opposed to short-term loans, is well worth the additional cost, because of advantages in terms of risk-sharing, access to intellectual property, impact on investment, and lesser vulnerability to capital flow reversal. Discusses the extent to which authorities control appropriate policy levers and concludes with a brief look at the composition of capital outflows from developing countries.